Increasing Public Awareness Through the Provision of Trash Bins and Information Boards at Karang Empat Beach - Alfitry, Nurul; Firmansyah, Erick; Hardianingsih, Ribi; Arman; Mutia Hairun Nisa; Sani; Muh. Zainal; Syaiful, Muhammad; Yuyun Anggraini; Hariono Hariono (MEKONGGA: Jurnal Pengabdian Masyarakat, 2024)
Indonesia, as an archipelagic country, boasts extensive and diverse coastal resources. Sustainable management of coastal areas is crucial to ensure long-term benefits for communities. One recently opened tourist destination is Karang Empat Beach, located in Ranokomea Village, West Poleang District, Bombana Regency. Despite its high tourism potential, the beach faces serious issues related to waste accumulation, particularly plastic waste, caused by a lack of visitor awareness and inadequate disposal facilities. To address this problem, a dedicated team conducted a series of activities, including the provision of trash bins, beach clean-up efforts, and the installation of informational boards to raise public awareness. The positive response from local authorities further supported these efforts. The results of these activities demonstrated a reduction in waste on the beach and an increase in public awareness about proper waste disposal. This study highlights the importance of collaboration between communities and management in maintaining cleanliness and ensuring the sustainability of tourist areas.